505. Mucosal and Systemic Humoral Immunity Differences between Sexes during Influenza Vaccination and Viral Challenge. (15th December 2022) - Giurgea, Luca T; Bean, Rachel; Han, Alison; Czajkowski, Lindsay; Cervantes-Medina, Adriana; Gouzoulis, Monica; Baus, Holly Ann; Reed, Susan M; Athota, Rani; Mateja, Allyson; Hunsberger, Sally; Kash, John; et al.
Abstract: Background: In previous influenza challenge studies we observed that the incidence of influenza symptoms was higher in women than in men, and that women experience more symptoms overall. Women also demonstrated lower neuraminidase (NA) inhibition (NAI) antibody titers than men after challenge and regression analysis suggested that NAI titers predict clinical outcomes. We sought to evaluate this using data from a more recent challenge study with more immunologically varied volunteers, while also assessing mucosal immunity. Methods: We obtained mucosal and serum samples from healthy adults. Half underwent intramuscular quadrivalent influenza vaccination followed by influenza A (H1N1) intranasal challenge while others just challenge alone. Antibody titers and clinical outcomes between sexes were compared. Results: No significant differences in shedding or symptom outcomes were observed between sexes. Similarly, no differences in systemic titers against NA or hemagglutinin (HA) were seen. Serum total IgG and IgA were also similar between sexes. Prior to vaccination, mucosal IgA titers were significantly lower against HA stalk and NA in women, but these differences disappeared after vaccination. In the unvaccinated group, lower nasal IgA titers were also seen in women pre-challenge. At 7 days post-challenge, differences in mucosal titers between sexes disappeared. However, at 56 days post-challenge, mucosal IgA titers against HA, HA stalk, and NA were all significantly lower in women. Conclusion: In contrast to our previous findings, no differences in clinical outcomes or systemic NAI titers were observed between men and women, possibly due to differences in underlying immunity between study populations or the lower sample size in this study. However, mucosal differences were noted with women having lower mucosal titers than men against HA stalk and NA at baseline. While influenza vaccination and challenge eliminated differences in the short term, they reappeared 8 weeks after challenge, with all nasal IgA antibody titers (HA, HA stalk, and NA) lower in women. Further studies are necessary to understand the differences in influenza disease and immunity between sexes. Disclosures: All Authors : No reported disclosures.